Penyuluhan Dampak Negatif Penyalanggunaan Narkotika Terhadap Kesehatan di Aceh Tamiang - Cut Khairunnisa; Sidrah Nadira, Cut (Academica : Jurnal Pengabdian Kepada Masyarakat, 2023)
There are at least three factors that influence students to consume narcotics, namely the family environment, school environment and community environment. Narcotics abuse among students is a serious problem because they are a productive age group and are the next generation to follow. Therefore, health counseling activities for students on drug abuse are needed on an ongoing basis. Responding to this problem, a lecturer at the Faculty of Medicine, Universitas Malikussaleh, has held legal counseling about drug abuse at Aceh Tamiang. This activity is a form of Higher Education Tridarma in which every member of the academic community performs community service to provide solutions to any problems being experienced by the community.